The effects of drying techniques on phytochemical contents and biological activities on selected bamboo leaves - Mohammad Amil Zulhilmi Benjamin; Shean, Yeaw Ng; Fiffy Hanisdah Saikim; Nor Azizun Rusdi (Molecular Diversity Preservation International, 2022)
The therapeutic potential of bamboos has acquired global attention. Nonetheless, the biological activities of the plants are rarely considered due to limited available references in Sabah, Malaysia. Furthermore, the drying technique could significantly affect the retention and degradation of nutrients in bamboos. Consequently, the current study investigated five drying methods, namely, sun, shade, microwave, oven, and freeze-drying, of the leaves of six bamboo species, Bambusa multiplex, Bambusa tuldoides, Bambusa vulgaris, Dinochloa sublaevigata, Gigantochloa levis, and Schizostachyum brachycladum. The infused bamboo leaves extracts were analysed for their total phenolic content (TPC) and total flavonoid content (TFC). The antioxidant activities of the samples were determined via the 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,20 -azino-bis (3-ethylbenzothiazoline-6- sulfonic acid) (ABTS), and ferric reducing antioxidant power (FRAP) assays, whereas their toxicities were evaluated through the brine shrimp lethality assay (BSLA). The chemical constituents of the samples were determined using liquid chromatography–tandem mass spectrometry (LC-MS/MS). The freeze-drying method exhibited the highest phytochemical contents and antioxidant activity yield, excluding the B. vulgaris sample, in which the microwave-dried sample recorded the most antioxidant and phytochemical levels. The TPC and TFC results were within the 2.69 ± 0.01–12.59 ± 0.09 mg gallic acid equivalent (GAE)/g and 0.77 ± 0.01–2.12 ± 0.01 mg quercetin equivalent (QE)/g ranges, respectively. The DPPH and ABTS IC50 (half-maximal inhibitory concentration) were 2.92 ± 0.01–4.73 ± 0.02 and 1.89–0.01 to 3.47 ± 0.00 µg/mL, respectively, indicating high radical scavenging activities. The FRAP values differed significantly between the drying methods, within the 6.40 ± 0.12–36.65 ± 0.09 mg Trolox equivalent (TE)/g range. The phytochemical contents and antioxidant capacities exhibited a moderate correlation, revealing that the TPC and TFC were slightly responsible for the antioxidant activities. The toxicity assessment of the bamboo extracts in the current study demonstrated no toxicity against the BSLA based on the LC50 (lethal concentration 50) analysis at >1000 µg/mL. LC-MS analysis showed that alkaloid and pharmaceutical compounds influence antioxidant activities, as found in previous studies. The acquired information might aid in the development of bamboo leaves as functional food items, such as bamboo tea. They could also be investigated for their medicinal ingredients that can be used in the discovery of potential drugs.